Reactivity of a Bicyclo[2.1.1]hexene Germylene towards Elemental Chalcogens. Issue 17 (20th July 2018) - Dong, Zhaowen; Schmidtmann, Marc; Müller, Thomas
Abstract : The reaction of stable hafnocene‐based bicyclo[2.1.1]hexene type germylene with elemental sulfur, selenium, and tellurium gives access to 2, 4‐dichalcogena‐1, 3‐digermetanes. These strongly colored four membered germanium heterocycles are produced as a mixture of cis and trans ‐isomers and are characterized by NMR and UV spectroscopy and by the results of an XRD analysis. Abstract :